Possibilidades de acompanhamento pedagógico de professores iniciantes frente aos desafios do trabalho em um instituto federal de educação, ciência e tecnologia - Schneiders, Patricia Mallmann (2017)
This research, developed within the framework of Professional Master's Program in Public Policies and Educational Management from Universidade Federal de Santa Maria (UFSM), during 2015 to 2017, focuses on the pedagogical monitoring (PM) of beginners teachers at a Federal Institute of Education, Science and Technology. As a goal, we seek to understand the possibilities for monitoring, which is realized by the Pedagogical Support Sector, through the work of beginning teachers at IFFar - Panambi Campus, in order to signal guidelines that may guide the of these teachers, in this case, the research product. The research problem consists of the following question: How can the demands evidenced in the work of beginning teachers at the Federal Institute Farroupilha - Panambi Campus, guide the work actions of the Pedagogical Support Sector (PSS) of this institution? In order answer this question, we are guided by three questions: 1) How is characterized the work of beginning teachers at Farroupilha Federal Institute - Panambi Campus? 2) How is the work of pedagogical monitoring, realized by the professionals from Pedagogical Support Sector (PSS) of IFFar - Panambi Campus? 3) Which demands are pertinent to the Pedagogical Support Sector in the orientation of teachers who begin to work at Farroupilha Federal Institute - Panambi Campus? The used methodology was based on pedagogical research (LANKSHEAR; KNOBEL, 2008), with quality approach (GATTI; ANDRÉ, 2010 and GHEDIN; FRANCO, 2011), and the analysis was based on the categorization process anchored by Grounded Theory (CHARMAZ, 2009). As information gathering instruments, we used individual interviews (MINAYO, 2006) and focus groups (BARBOUR, 2009 and ZAMBON, 2015). In order to base the theoretical-conceptual and theoretical-practical contributions in this work, we use as references Canário (2006) and Santos (2011), to emphasize the current challenges posed to the contemporary school; Tardif; Lessard (2005) and the conception of teaching work; Garcia (2009), Huberman (2000), Tardif (2002) and Imbernón (1998) and the definition of beginner teacher; Placco; Almeida and Souza (2011), to approach the role and the importance of the Pedagogical Coordinator for school daily life; Pacheco (2011), to emphasize about the institution and the affirmation of FIs in the country, among others. In the conclusions, we systematize the collected information and present some constructions. In this sense, we verified that the teaching work has characteristics, some more lasting and others sporadic, which were resulting from the didactic- pedagogical and organizational structure of the campus, in the same way that factors unrelated to the Institution and to teaching, as personal and professional aspects influence and integrate the teaching work. We also, found that teachers do not consider the traffic through the different levels and modalities of teaching as a practical and epistemological problem; on the contrary, they consider it a challenge that leads them to build and to share knowledge with audiences of different ages, particularities and interests. We also verified, that, in the same way that there is no systematized systematization of actions aimed at the qualification of the teaching staff at Panambi Campus, there is also no systematization in favor of the acceptance of the teachers who begin to work at this place. In view of this, there is a gap in the work of this context, since the fact that the campus does not have a training proposal, it leaves up to each one to elaborate his own formative trajectory, it is aggravating as the local culture becomes the main reference to teachers, when they start to teach at Federal Institute and to carry out their own practices. In view of this framework, we highlight another gap related to PSS work, since workers spend most of their time in bureaucratic and routine activities. That is, there is a specific Sector for pedagogical issues, but these actions are not realized só much, it contributes that the work of the Sector was understood as a purely operational work, of academic routine organization, institutional and administrative demands. Finally, we conclude that, due to the situation presented, there is still a long way to go for PPS in order to constitute itself as an essentially pedagogical support sector. However, it encompasses a range of needs and demands presented by teachers, as well as enabling us to constitute, as a group of the Pedagogical Sector, some guidelines with a view to minimizing the challenges of teachers (product of the research), allows us a possibility of acting and resizing our actions.